Making a difference in the real world? A meta-analysis of the quality of use-oriented research using the Research Quality Plus approach. Issue 2 (4th September 2018) - McLean, Robert K D; Sen, Kunal
Abstract: High-quality, use-oriented, and well-communicated research can improve social outcomes in low- and middle-income countries and, by doing so, accelerate development progress. We provide a meta-analysis of research supported by Canada's International Development Research Centre. We use a large and unique data set that comprises 170 research studies undertaken over the period 2010–2015. The research examined spans multiple disciplines of the social and natural sciences and was conducted across the globe, with the majority in Africa, Asia, Latin America, the Caribbean, and the Middle East. The evaluative framework we use— Research Quality Plus, RQ+ —incorporates argumentation espoused in the Leiden Manifesto . As such, this article presents a case study of doing research evaluation differently and what the results can look like for research policymakers. Our analysis suggests that contrary to conventional wisdom, there is no clear trade-off between the rigor and the utility of research and that research capacity-strengthening effort is positively correlated with the scientific merit of a project. We conclude that those located closest to a development challenge are generally those best positioned to innovate a solution. The results present novel evidence for those supporting, using, and doing research for development.